The Impact of COVID-19 Pandemic on Ocular Oncology Services at Cipto Mangunkusumo Hospital, Indonesia - Anggraini, Neni; Nursanti, Hanifah Rahmani; Mahyuddin, Mutmainah (http://dharmais.co.id/, 2024)
Background:: Delay of diagnosis and treatment in ocular oncology services due to the COVID-19 pandemic is very disadvantageous. This study aimed to evaluate the impact of COVID-19 on new patients with suspected eye tumors in terms of volume, characteristics, and waiting time for a procedure. Methods: : A retrospective study based on hospital records of new patients was held in the ocular oncology clinic of Cipto Mangunkusumo Hospital, a tertiary eye care center in Jakarta, Indonesia. Patients were analyzed descriptively based on three time periods: pre-COVID-19, COVID-19 social restriction, and post-COVID-19 social restriction. Each patient was stratified according to case priority during the COVID-19 pandemic suggested by Indonesia’s Ophthalmologist Association (IOA). Results: During the COVID-19 social restriction between March to June 2020, new patient volume decreased by 73.1%, with a 75.5% decline in referrals from the governmental hospital. Elderly, pediatric, and highly educated patients were less likely to visit the clinic. Patients with acute onset, invasive or metastatic tumors, and advanced T-stage were more likely to be referred to the hospital. Third-priority cases referred with a lower ratio during COVID-19 social restriction (29% vs 44.9% in pre-COVID-19 and 35.1% in post-COVID-19 social restriction) and had to wait longer for the procedure (41 (18–60) days vs 28.5 (11–63) days in pre-COVID-19 and 16.5 (7–67) days in post-COVID-19 social restriction). Conclusions: : As the healthcare service was overwhelmed by COVID-19 patients, referral to ocular oncology services was severely disrupted, particularly in elderly, pediatric, and early T-stage patients. Strategies are needed to ensure that highly prioritized cases may access the services.